Involvement of the Haemophilus ducreyi gmhA Gene Product in Lipooligosaccharide Expression and Virulence - Bauer, Beth A. (American Society for Microbiology, 1998)
The lipooligosaccharide (LOS) present in the outer membrane of Haemophilus ducreyi is likely a virulence factor for this sexually transmitted pathogen. An open reading frame in H. ducreyi 35000 was found to encode a predicted protein that had 87% identity with the protein product of the gmhA (isn) gene of Haemophilus influenzae. In H. influenzae type b, inactivation of the gmhA gene caused the synthesis of a significantly truncated LOS which possessed only lipid A and a single 2-keto-3-deoxyoctulosonic acid molecule (A. Preston, D. J. Maskell, A. Johnson, and E. R. Moxon, J. Bacteriol. 178:396–402, 1996). The H. ducreyi gmhA gene was able to complement a gmhA-deficient Escherichia coli strain, a result which confirmed the identity of this gene. When the gmhA gene of H. ducreyi was inactivated by insertion of a cat cartridge, the resultant H. ducreyi gmhA mutant, 35000.252, expressed a LOS that migrated much faster than wild-type LOS in sodium dodecyl sulfate-polyacrylamide gel electrophoresis. When the wild-type H. ducreyi strain and its isogenic gmhA mutant were used in the temperature-dependent rabbit model for dermal lesion production by H. ducreyi, the gmhA mutant was found to be substantially less virulent than the wild-type parent strain. The H. ducreyi gmhA gene was amplified by PCR from the H. ducreyi chromosome and cloned into the pLS88 vector. When the H. ducreyi gmhA gene was present in trans in gmhA mutant 35000.252, expression of the gmhA gene product restored the virulence of this mutant to wild-type levels. These results indicate that the gmhA gene product of H. ducreyi is essential for the expression of wild-type LOS by this pathogen.